Develop Your Case! How Controversial Cases, Subcases, and Moderated Cases Can Guide You Through Mixed Methods Data Analysis - Schoonenboom, Judith (Frontiers in Psychology, 2019)
In this article, we present mixed methods data analysis in educational research as a process of case development. We define a case as a theoretical construct that is developed through iterative and spiraling cycles of interaction between ideas and evidence. On a larger scale, cases develop over a period of several years or even decades, involving many studies. But cases also develop within a much smaller timescale, within studies. Development of cases within mixed methods studies is the theme of this article. We define the purpose for any mixed methods study as to acquire detailed insight into the case, subcases, and the way the subcases are moderated. Developing a case starts with identifying a phenomenon that will be the object of research. A phenomenon can be investigated empirically once researchers are able to identify specific contexts, localized in time and space, in which the phenomenon occurs. At that point, an underdeveloped case has come into being, and the specific contexts in which the case occurs are called instantiations of the case. Connected to each case are claims, statements about the case that are used to describe the case more precisely and to distinguish cases from non-cases. Developing these claims is the aim of the analysis processes. Case development includes three different research processes—namely, resolving a controversial case, developing subcases, and developing a moderated case. Case development typically occurs in this order; however, each of these processes can but do not need to be present. When cases develop, they typically become controversial for some time. Some research studies support a specific claim, while other research studies refute this claim. Next to claims that apply to all instantiations of a case, claims may be developed that apply to only some of the case’s instantiations. In that case, claims are used to distinguish subcases. A moderated case is developed when researchers come to understand under which circumstances their claim does and does not apply, which leads to their subcases. This is called "moderation" of their claim.